Tribological Properties Of Palm Oil-Based Grease With Nano Particle Additive - Lee, Ann Yen (Universiti Sains Malaysia, 2021)
The harmful environmental effect of the widespread use of mineral oil and synthetic oil as commercial lubricant greases has been raising concerns in the community. Therefore, the sustainable development of vegetable oil-based bio-lubricants is important to promote the use of biodegradable greases to replace commercial greases. A proposal was made that thickeners and nanoparticles as additives have the capability to improve the tribological properties of the vegetable oil- based lubricants. In this study, the tribological properties of palm oil-based greases which were formulated with refined palm olein, lithium stearate soap and copper (Cu) nanopowder were evaluated experimentally using a four ball tribotester. Commercially available food grade grease and biodegradable mineral grease were also tested for comparison. The tribological wear tests were conducted at 75℃ temperature and 1200rpm speed under a normal load of 40kg for 1 hour as per ASTM D2266. An additional set of test at 100℃ was carried out to study the effect of temperature on the lubricant properties. The physical properties of the lubricant including viscosity, viscosity index and flash temperature parameter and the tribological properties including frictional torque, friction coefficient, wear scar diameter, surface wear characteristics, and surface roughness were investigated. These findings showed that the formulated palm oil-based grease exhibited finer tribological properties in terms of higher viscosity index and lower frictional torque, friction coefficient, oxidation effect and surface roughness as compared with food grade grease and biodegradable mineral grease. However, the formulated palm oil-grease exhibited less desired properties in terms of wear scar diameter and flash temperature parameter. From the findings, it can be inferred that the tribological characteristics of the palm oil-based bio-lubricants greases are comparable and competitive with the commercial greases.